Preparation of Nickel Ferrite/Carbon Nanotubes Composite by Microwave Irradiation Technique for Use as Catalyst in Photo-Fenton Reaction - Caroline Rigo; Eric da Cruz Severo; Marcio Antonio Mazutti; Guilherme Luiz Dotto; Sérgio Luiz Jahn; André Gündel; Márcia Maria Lucchese; Osvaldo Chiavone-Filho; Edson Luiz Foletto (Materials Research, 2017)
Nickel ferrite/multi-walled carbon nanotubes (NiFe2O4/MWCNTs) composite has been rapidly synthesized via microwave irradiation technique. The structural properties of the product was investigated by X-ray diffraction (XRD), N2 adsorption/desorption isotherms, thermogravimetric analysis (TGA), Raman spectroscopy and, scanning electron microscopy (SEM). Catalytic behavior of the composite material on the advanced photo-Fenton degradation of Amaranth dye was evaluated. The synthesis conditions employed on the microwave system were: temperature (235 °C), power (500 W), pressure (600 psi) and irradiation time (30 min). Characterization results showed the formation of hybrid material, containing a predominantly microporous structure, with surface area and total pore volume of 54 m2 g-1 and 0.2249 cm3 g-1, respectively. The composite exhibited higher catalytic activity compared to the pure NiFe2O4, reaching 100% of decolorization at 60 min of reaction, which can be attributed to a synergism between NiFe2O4 and MWCNTs. Therefore, NiFe2O4/MWCNTs composite can be used as a promising photo-Fenton catalyst to degrade Amaranth dye from aqueous solutions.